2020
DOI: 10.3390/ijerph17186594
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic and Utilitarian Performances as Determinants of Mental Health and Pro-Social Behaviors among Volunteer Tourists

Abstract: International volunteer tourism is an emerging and sustainable trend of the global tourism industry. In this study, we attempted to provide a clear comprehension of volunteer tourists’ mental health increase and pro-social intention formation. A survey method and quantitative approach were used. Our result from the structural analysis showed that hedonic and utilitarian performances, mental health, and volunteer tourism engagement had significant associations and that these relationships contributed to improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This connection with nature has been shown to enhance users' hedonic experiences, promoting feelings of calmness, rejuvenation, and an overall sense of happiness. This is supported by Han et al, (2020) and Zemke et al (2018) that the hotel's green practices significantly increased values and pro-environmental intentions, and both hedonic and utilitarian values. Delivering personalized and attentive service that caters to individual needs, preferences, and desires can create a positive emotional connection and enhance the hedonic experience.…”
Section: Fig 2 -Network Of Coding and Participants' Responses On Sust...mentioning
confidence: 82%
“…This connection with nature has been shown to enhance users' hedonic experiences, promoting feelings of calmness, rejuvenation, and an overall sense of happiness. This is supported by Han et al, (2020) and Zemke et al (2018) that the hotel's green practices significantly increased values and pro-environmental intentions, and both hedonic and utilitarian values. Delivering personalized and attentive service that caters to individual needs, preferences, and desires can create a positive emotional connection and enhance the hedonic experience.…”
Section: Fig 2 -Network Of Coding and Participants' Responses On Sust...mentioning
confidence: 82%
“…In addition, this article considered that a unification of the indicators that measure religiosity is necessary since the results vary widely according to the selected indicators [ 13 ]. Other research has demonstrated that the hedonic and utilitarian performances of volunteer tourism significantly and positively contribute to increasing travellers’ mental health, which ultimately enhances their prosocial intentions [ 14 ]. Last, community integration of persons with mental disorders was another topic addressed in a Korean sample [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned by Andargie et al (2020), evaluating happiness as a social characteristic focuses on understanding and enhancing the overall happiness levels of individuals through the built environment. Happiness is a common social behaviour in any evaluation of products, facilities or services and is regarded as hedonic consumption (Han et al , 2020; Zemke et al , 2018). Happiness is closely connected to physical health and stress reduction, as it is capable of creating an attractive work environment that can contribute to employee retention and foster a positive organizational culture.…”
Section: The Analysis and Discussion Of Findingsmentioning
confidence: 99%